2009
DOI: 10.1029/2007jb005572
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric electrical imaging of the Deccan trap covered region of western India

Abstract: We present here the results of magnetotelluric (MT) studies carried out along a 330 km long NE‐SW trending traverse from Daulatabad at the northeastern end to Koyna on the southwestern end across the Deccan volcanic province (DVP) in western India. The 2‐D MT modeling results obtained along this traverse together with those from other MT traverses in this area are examined and integrated with the results from deep seismic sounding, 3‐D teleseismic tomography, and heat flow studies. The deep geoelectric section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 88 publications
3
23
0
Order By: Relevance
“…Three-dimensional modelling studies (Patro & Sarma 2009) conducted in similar situations have shown that the coast effect is stronger in the case of the TM mode than the TE mode. According to Gokarn et al (2004), both TE and TM modes used in two-dimensional modelling show very marginal variations of 0.5Á0.1 in phase and nearly 10% in apparent resistivity for the sites close (ca.…”
Section: Three-dimensional Forward Modellingmentioning
confidence: 99%
“…Three-dimensional modelling studies (Patro & Sarma 2009) conducted in similar situations have shown that the coast effect is stronger in the case of the TM mode than the TE mode. According to Gokarn et al (2004), both TE and TM modes used in two-dimensional modelling show very marginal variations of 0.5Á0.1 in phase and nearly 10% in apparent resistivity for the sites close (ca.…”
Section: Three-dimensional Forward Modellingmentioning
confidence: 99%
“…1). For the 2D interpretation reported in Patro et al (2005a) and Patro and Sarma (2009) sites were divided into two groups, with impedances from the southern sites (1-18) rotated to 50°W of N, with the remaining sites rotated to 65°W of N. This coordinate system is consistent with the strike (NW-SE) evident in the regional geology (Arya et al, 1995;Peshwa and Kale, 1997). For the EK profile, the regional strike direction was computed using the tensor decomposition techniques of and Becken and Burkhardt (2004).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 53%
“…We first summarize briefly the 2D inversion results presented in Patro et al (2005a,b) and Patro and Sarma (2009), and relate these to the principal features evident in pseudo-sections for the two profiles. The 2D inversion of TE and TM data was carried out using the nonlinear conjugant gradient (NLCG) algorithm of .…”
Section: Review Of 2d Inversion Resultsmentioning
confidence: 99%
“…Suggested conductive agents include graphite in the Slave Craton (Jones et al, 2001) , hydrated minerals in the Kaapvaal Craton (Evans et al, 2011) and compositional changes of mantle minerals in the Dharwar Craton (Patro et al, 2009). New results from the Gawler Craton see a similar feature underlying the surface expressions of the Gawler Range Volcanics and the Hiltaba Suite (Thiel and Heinson, 2013).…”
Section: Introductionmentioning
confidence: 76%